The impact of the broadcast legislative reforms on the newsroom staff's perceptions of the Zambia National Broadcasting Corporation (ZNBC)'s editorial operations and news content - Hamasaka, Clayson (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2008)
The 1980s and 1990s saw major changes in the political landscape of the media in many countries that were either reverting or emerging from repressive nondemocratic regimes. Among the notable changes in media industry was the opening up of the national airwaves, which had been a state monopoly, to private sector and community participation. The democratic dispensation also put state broadcasters in the spot-light regarding their editorial content which was previously 'institutionalised' as belonging to the ruling regimes. This study set out to investigate the extent to which broadcasting reform legislation meant to address the unfair coverage of contending voices on Zambia's public broadcaster has had an impact in reversing the situation in the newsroom. Using qualitative methods of investigation, the study established that while the ZNBC staff understand aspects of their role in their newsroom in relation to the principles of public service broadcasting and in line with the enacted legislation, they perceive that, in practice, they have to ensure that the news content still remains a reserve of a few voices in favour of the ruling regime. This was evidenced by testimonies from the news staff's complaints of continued editorial interference in their work by government leaders and government appointed gatekeepers, as well as selfcensorship. The study recommends, among other things, the full implementation of the recently enacted laws on the operations of ZNBC in order to achieve some minimum levels of being a public broadcaster. It further recommends a serious re-orientation of the ZNBC newsroom and management staff to the current legislative requirements so as to shift their mindset away from their traditionally-held views of thinking that news at that station is only for the ruling regime.
Keywords: Zambia National Broadcasting Corporation; Public broadcasting -- Zambia; Mass media -- Management -- Zambia; Broadcasting -- Law and legislation -- Zambia; Broadcasting -- Political aspects -- Zambia